Achieving Ultrahigh Molecular Weights with Diverse Architectures for Unconjugated Monomers through Oxygen‐Tolerant Photoenzymatic RAFT Polymerization. Issue 49 (29th September 2020) - Li, Ruoyu; An, Zesheng
Abstract: Achieving well‐defined polymers with ultrahigh molecular weight (UHMW) is an enduring pursuit in the field of reversible deactivation radical polymerization. Synthetic protocols have been successfully developed to achieve UHMWs with low dispersities exclusively from conjugated monomers while no polymerization of unconjugated monomers has provided the same level of control. Herein, an oxygen‐tolerant photoenzymatic RAFT (reversible addition‐fragmentation chain transfer) polymerization was exploited to tackle this challenge for unconjugated monomers at 10 °C, enabling facile synthesis of well‐defined, linear and star polymers with near‐quantitative conversions, unprecedented UHMWs and low dispersities. The exquisite level of control over composition, MW and architecture, coupled with operational ease, mild conditions and environmental friendliness, broadens the monomer scope to include unconjugated monomers, and to achieve previously inaccessible low‐dispersity UHMWs. Abstract : Well‐defined polymers with ultrahigh molecular weight were achieved with an oxygen‐tolerant photoenzymatic RAFT polymerization performed at 10 °C. The facile synthesis, in aqueous solution and without prior deoxygenation, produces well‐defined linear and star polymers with near‐quantitative conversions, ultrahigh molecular weight, and low dispersities.